Museomics: Phylogenomics of the Moth Family Epicopeiidae (Lepidoptera) Using Target Enrichment. Issue 2 (21st April 2021) - Call, Elsa; Mayer, Christoph; Twort, Victoria; Dietz, Lars; Wahlberg, Niklas; Espeland, Marianne
Abstract: Billions of specimens can be found in natural history museum collections around the world, holding potential molecular secrets to be unveiled. Among them are intriguing specimens of rare families of moths that, while represented in morphology-based works, are only beginning to be included in genomic studies: Pseudobistonidae, Sematuridae, and Epicopeiidae. These three families are part of the superfamily Geometroidea, which has recently been defined based on molecular data. Here we chose to focus on these three moth families to explore the suitability of a genome reduction method, target enrichment (TE), on museum specimens. Through this method, we investigated the phylogenetic relationships of these families of Lepidoptera, in particular the family Epicopeiidae. We successfully sequenced 25 samples, collected between 1892 and 2001. We use 378 nuclear genes to reconstruct a phylogenetic hypothesis from the maximum likelihood analysis of a total of 36 different species, including 19 available transcriptomes. The hypothesis that Sematuridae is the sister group of Epicopeiidae + Pseudobistonidae had strong support. This study thus adds to the growing body of work, demonstrating that museum specimens can successfully contribute to molecular phylogenetic studies.